Revitalisasi Bangunan Cagar Budaya Gedung Juang Tambun sebagai Museum Digital Kabupaten Bekasi, 2019-2021 - Imbron, Imbron; Falah, Miftahul; Kartika, Nyai (Universitas Hamzanwadi, 2024)
This research was written to provide information and education about changes in the function of the Juang Tambun Building as a Digital Museum and the use of abandoned or neglected cultural heritage buildings. This research uses the Historical Method. In this method there are four heuristic stages, internal criticism and external criticism, interpretation, and historiography. The results of this research, the revitalization of the Juang Tambun Building as the Bekasi Regency Digital Museum, has had a positive impact on the surrounding community. The Juang Tambun Building is officially managed directly by the Bekasi Regency Culture, Youth, and Sports Department. In 2019, the Juang Tambun Building before being revitalized was only a cultural heritage building with no attractions to visit. In 2021, the Juang Tambun Building will officially become a digital museum that provides information about the history of the Bekasi Regency. The revitalization of the Juang Tambun Building has an influence on the economic aspects, educational aspects, and tourism aspects of the people of Bekasi Regency.